Analysis Of Hadiths Related To Literature (Poetry) In Imam Al-Tirmidhi's Al-Syamail Al-Muhammadiyyah - Nurhasma Muhamad Saad; Ab Adly Rabbanie Ab Rahim; Wan Moharani Mohammad; Yee Chin Yip; Margaret Anthoney (Usuli Faqih Research Centre PLT., 2025)
Index (Tier 3)